Lag associations of gestational phthalate exposure with maternal serum vitamin D levels: Repeated measure analysis. (July 2022) - Gao, Hui; Tong, Juan; Zhu, Bei-bei; Chen, Yao; Ye, Ao-xing; Huang, Kun; Liang, Chun-mei; Wu, Xiao-yan; Sheng, Jie; Jin, Zhong-xiu; Zhu, Peng; Hao, Jia-hu; et al.
Abstract: Few studies have investigated the relationships between gestational phthalate exposure and maternal circulating vitamin D. In the Ma'anshan birth cohort, 3265 pregnant women were included. Each woman provided up to three urine and serum samples for measurement of phthalates and 25(OH)D and calcium, respectively. Linear mixed models were performed to analyse the association between phthalate metabolites and 25(OH)D and calcium. Stratified analyses of the relationship between phthalates and 25(OH)D by urine collection season were conducted. Finally, the post hoc lag effect of phthalate exposure on 25(OH)D was determined if longitudinal associations were significant. Some phthalate metabolites were associated with increased 25(OH)D but with decreased calcium. Furthermore, the relationship of phthalate exposure with 25(OH)D varied with urine collection season. Phthalate metabolites collected in summer and autumn were associated with an increase in 25(OH)D, while monobenzyl phthalate collected in winter and spring was inversely associated with 25(OH)D. Finally, high-molecular-weight phthalates had lag associations with 25(OH)D with a 1-trimester lag period. Low-molecular-weight phthalates exhibited lag associations with 25(OH)D with a 2-trimester lag period. In conclusion, the positive cross-sectional correlation between phthalate metabolites and 25(OH)D was partly affected by urine collection season. This study suggested that gestational phthalate exposure would have a lag association with maternal 25(OH)D levels. Graphical abstract: Image 1 Highlights: Phthalate metabolites (PAEs) were measured in multiple urine samples during pregnancy. Positive cross-sectional relations between PAEs and 25(OH)D were shown. Relationships between PAEs and 25(OH)D varied by season of urine collection. High molecular weight PAEs had a lag association with 25(OH)D with a 1-trimester lag period. Low molecular weight PAEs had a lag association with 25(OH)D with a 2-trimester lag period.